Ethanol elimination rates at low concentrations based on two consecutive blood samples. (September 2016) - Høiseth, Gudrun; Wiik, Elisabeth; Kristoffersen, Lena; Mørland, Jørg
Highlights: Ethanol elimination rates are less studied at low blood alcohol concentrations. Drunk drivers show high elimination rates during high blood alcohol concentrations. In a drunk driver population, first order ethanol kinetics prevails below 0.19 g/kg. The first order kinetics do not differ substantially from healthy volunteers. Abstract: Introduction: For ethanol, the elimination curve change from apparent zero to apparent first order kinetics at low blood alcohol concentrations (BACs). This is less studied than elimination at higher BACs, and knowledge about this low BAC elimination is especially missing in drunk drivers representing a population with a high frequency of heavy drinkers with increased rate of ethanol metabolism. The aim of this study was to investigate the point at which elimination rates turns from zero to first order kinetics and the exact elimination rates at the very low BAC intervals in drunk drivers. Methods: Two consecutively collected samples from suspected drunk drivers were used. All samples were analyzed by two headspace gas chromatography flame ionization detector methods (limit of quantification = 0.04 g/kg). The elimination rates at BACs below 0.25 g/kg (study group, n = 175) was studied in detail, and compared to the elimination rates in a moderate BAC reference group ( n = 789) as well as a high BAC reference group ( n = 4435). Results: There were no differences in age, gender and drivings occurring during night-time between the study group and the reference groups. The mean elimination rates were stable at 0.18–0.19 g/kg/h from a BAC of 4.0 g/kg and until BAC in the first blood sample fell below 0.19 g/kg. At BACs below 0.19 g/kg, the mean elimination rate gradually declined from 0.163 g/kg/h to the lowest elimination rate of 0.083 g/kg/h. There was no relation between the concentration of ethanol and elimination rate at BACs above 0.19 g/kg (Pearson's r = 0.035, p = 0.3), but there was a strong relation between concentration of ethanol and elimination rate at BACs below 0.19 g/kg (Pearson's r = 0.56, p < 0.001). Conclusion: In conclusion, the present study showed that in a population of drunk drivers, the shift from zero order to first order kinetics occurs when BAC falls below 0.19 g/kg. Below this points, the present study indicate that drunk drivers show elimination rates comparable to the normal population. These results could assist in back-calculations in cases of drunk driving involving low BACs.